Famous and (Infamous) Workplace and Community Training A Social History of Training and Development - Kopp, David M. (Palgrave Macmillan US, 2018)
This book explores the social history of training and development and describes how ordinary training systems were linked to extraordinary events. Using instrumental case studies, the author explores the direct and indirect motives behind famous and infamous training systems of history such as the methods used by John Lennon and Paul McCartney in the Beatles, those used by the Third Reich in training forced labor, and in the social guidance films of the 1950's, among others. This book links modern-day themes of corporate and community social responsibility and social justice to historical cases of workplace and community training; in addition, it offers a unique view of business history that students and scholars can relate to, and contributes to a more thorough and robust inquiry into critical human resource development, ethics in the workplace, and the nature of training adults, in general.